PENGARUH METODE PROBLEM BASED LEARNING TERHADAP KEAKTIFAN PESERTA DIDIK PADA MATA PELAJARAN PAI KELAS VII DI SMPIT HARAPAN UMAT KARAWANG - Jihan Fhajri; Abdurrohim; Siti Khulasoh (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
This This study was motivated by the still-low level of student engagement in Islamic Religious Education (IRE) classes in the seventh grade at SMPIT Harapan Umat Karawang. The learning process, which tends to be teacher-centered, results in students being less actively involved in learning activities. Therefore, a teaching method is needed that can encourage student engagement, one of which is through the implementation of Problem-Based Learning (PBL). This study aims to determine the effect of using the PBL method on student engagement. The method used is a quantitative approach with an experimental research design. The population in this study consists of all seventh-grade students, with the sample selected using purposive sampling. Data collection was conducted through observation, questionnaires, and documentation. The results of the study indicate that the implementation of the PBL method is effective in increasing student engagement in learning. Students appeared more confident in expressing their opinions, active in group discussions, and more engaged in the problem-solving process. This indicates that the PBL method has a positive influence on student learning engagement. Thus, the Problem-Based Learning method can be an effective alternative for creating more active and meaningful learning, particularly in the subject of Islamic Religious Education.